1970
DOI: 10.1136/adc.45.243.702
|View full text |Cite
|
Sign up to set email alerts
|

The Normal Borders of the Liver in Infancy and Childhood: Clinical and X-ray Study

Abstract: Deligeorgis, D., Yannakos, D., Panayotou, P., and Doxiadis, S. (1970). Archives of Disease in Childhood, 45, 702. The normal borders of the liver in infancy and childhood. Clinical and x-ray study. In 365 healthy infants and children the normal range of the liver borders was defined by clinical and x-ray examination. It was found that in supine position and at the end of expiration the liver edge projects considerably below the costal margin in newborns and infants, and as the age increases the liver edge appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0
2

Year Published

1971
1971
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 1 publication
0
6
0
2
Order By: Relevance
“…The measurement of spleen length was the optically maximal distance at the hilum on the longitudinal coronal view (between the most supero-medial and the most infero-lateral points) as the spleen length at the hilum is considered the most reproducible linear measurement (10). The liver length was measured with the child in supine position and the section level along the MCL was determined by simultaneous demonstration of the right kidney as per standard methodology (11).…”
Section: Methodsmentioning
confidence: 99%
“…The measurement of spleen length was the optically maximal distance at the hilum on the longitudinal coronal view (between the most supero-medial and the most infero-lateral points) as the spleen length at the hilum is considered the most reproducible linear measurement (10). The liver length was measured with the child in supine position and the section level along the MCL was determined by simultaneous demonstration of the right kidney as per standard methodology (11).…”
Section: Methodsmentioning
confidence: 99%
“…Para melhor avaliação clínica, é proposto mensurar o comprimento hepático ("liver span") na linha hemiclavicular, ou seja, a distância entre as superfícies hepáticas superior e inferior, determinadas pelo método da percussão (6,12) ou percussãopalpação (4,5,7,13) .…”
unclassified
“…Estudos de mensuração hepática têm sido realizados em adultos e crianças, utilizando-se radiografia (13,(17)(18)(19) , cintilografia (1,3,14,20,21) , tomografia computadorizada (22) e ultra-sonografia (9,10,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41) .…”
unclassified
“…In the first part of our study (Deligeorgis et al, 1970) we defined the upper and lower borders of the liver in 350 healthy children, between birth and 16 years, by percussion and palpation. It was found that in the supine position and at the end of expiration the liver may project below the costal margin as much as 3 5 cm, the projection decreasing with age.…”
mentioning
confidence: 99%